2023
DOI: 10.1139/cjss-2023-0030
|View full text |Cite
|
Sign up to set email alerts
|

No differences in soil structure under winter wheat grown in different crop rotational positions

Jessica Arnhold,
Dennis Grunwald,
Henning Kage
et al.

Abstract: Yield decline in wheat grown after wheat is frequently attributed to fungal disease occurrence, but it is also found without visible disease infection. Thus it is hypothesized, that other factors such as N supply or soil structural degradation may lead to wheat yield decline when grown after wheat. The aims of this study were to analyze if (i) the crop rotational position of winter wheat causes differences in soil structure at the beginning of the growing season and (ii) the soil structure is related to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…(2005) suggested a modified soil structure as a reason for an effect of different pre-crops on the root system of the following crop. However, in April, no differences in soil structure in our field trial were found between the crop rotational positions investigated ( Arnhold et al., 2023 ).…”
Section: Discussionmentioning
confidence: 66%
“…(2005) suggested a modified soil structure as a reason for an effect of different pre-crops on the root system of the following crop. However, in April, no differences in soil structure in our field trial were found between the crop rotational positions investigated ( Arnhold et al., 2023 ).…”
Section: Discussionmentioning
confidence: 66%
“…The correlation of seminal root number only after an OSR precrop could be due to the comparatively reduced nutrient pressure when grown after OSR 54 , which has different nutritional demands, favouring plants with increased seminal roots to take quick advantage of the increased nutrients available. Differences in biopores could also explain the link between yield and seminal root number, as seminal roots require easy penetration for more effective use 55 , although a recent study has not shown any difference in soil structure between the two precrops used in this study 56 . As there are differences in the soil characteristics and nutrient conditions between the regions, it stands to reason that these differences, and thus potential root architectural advantages may be heightened or nullified depending on the environment.…”
Section: Discussionmentioning
confidence: 82%
“…These patterns in the root distribution over depth may be attributed to the soil's physical structure from both monoculture and rotational wheat. However, in the study conducted by Arnhold et al (2023a) in Harste over two years, no differences in soil structural parameters (i.e., bulk density, total pore volume, air and field capacity, and aggregate stability) were found for an early sampling in April (BBCH 30) over three soil depths under wheat grown in different crop rotational positions.…”
Section: Microbiome Response To Soil Depthmentioning
confidence: 86%
“…Monoculture is commonly linked to a decline in agricultural productivity and yield performance over time compared with systems that use diversified crop species in rotation (Smith et al, 2023). Arnhold et al (2023a) studied the effects of crop rotational position on wheat biomass in the same field plots in Harste. They found, on average, 54% higher aboveground biomass in wheat following winter oilseed rape compared with wheat monoculture in early plant stage BBCH 30, confirming earlier studies by Sieling et al (2005); Sieling et al (2007).…”
Section: Monoculture Impacts the Abundance Diversity And Composition ...mentioning
confidence: 99%